Parasitism versus mutualism in the ant-garden parabiosis between Camponotus femoratus and Crematogaster levior - Vantaux, A; Dejean, A; Dor, A; Orivel, J (Insectes sociaux, 2007)
Ant-gardens represent a special type of association between ants and epiphytes. Frequently, two ant species can share the same nest in a phenomenon known as 'parabiosis', but the exact nature (i.e., mutualistic or parasitic) of this interaction is the subject of debate. We thus attempted to clarify the mutual costs and benefits for each partner (ants and plants) in the Crematogaster levior/Camponotus femoratus ant-garden parabiosis. The ants' response to experimental foliar damage to the epiphytes and to the host tree as well as their behavior and interactions during prey capture were investigated to see if the purported parasitic status of Cr. levior could be demonstrated in either the ant-ant or in the ant-plant interactions. The results show that both species take part in protecting the epiphytes, refuting the role of Cr. levior as a parasite of the ant-garden mutualism. During capture of large prey Ca. femoratus took advantage from the ability of Cr. levior to discover prey; by following Cr. levior trails Ca. femoratus workers discover the prey in turn and usurp them during agonistic interactions. Nevertheless, the trade-off between the costs and benefits of this association seems then to be favorable to both species because it is known that Cr. levior benefits from Ca. femoratus building the common carton nests and furnishing protection from vertebrates. Consequently, parabiosis can then be defined as the only mutualistic association existing between ant species, at least in ant-gardens.